Análise técnico-econômica sobre a viabilidade de produção de etanol lignocelulósico - Lewiski, Daniel de Vargas (2020)
The world energy scenario presented over the past few years rates biofuels as one of the main alternatives for reducing the consumption of fossil fuels, since a view to reducing damage to the environment and diversifying the world economic matrix is necessary. First generation bioethanol encounters certain social and economic barriers in relation to the use of food as a raw material, such as lignocellulosic ethanol with great energy potential for the coming years, since this biofuel is produced using biomass that are abundant and diverse materials in the biosphere. However, a large-scale production of lignocellulosic ethanol is still a challenge, as its production process requires a high investment and has a high operating cost. Thus, the objective of this study is to measure and analyze each stage of the production process of lignocellulosic ethanol through a bibliometric research of market economy tests, studies and techniques of technical production, raw materials, inputs and integration with other productions. In addition, check how the price trends of raw materials and other products that influence the promotion of first and second generation ethanol in Brazil for the coming years, using time series to verifying economic viability, risk analysis and projections for possible scenarios. In relation to the studies analyzed, 54.9% considered only raw material or the most important operating cost component, 25.6% considered raw material and enzymes and 13.4% only enzyme. The study you chose or the lowest minimum selling price of ethanol (0.48 $ / l) used bamboo as the main raw material, this result was followed by wood (0.49 $ / l) and empty fruit clusters (0.49 $ / l). The price of raw materials and enzymes is the most important factor to make the production of lignocellulosic ethanol feasible. The forecast about the price of first generation ethanol in 2025 showed that there is a great tendency for an increase (10-20%) in relation to 2019, thus, the scenario for the growth of cellulosic ethanol production in Brazil it is optimistic and with success indicators.